Topical anesthesia - Mritunjay Kumar; Rajiv Chawla; Manish Goyal (Wolters Kluwer Medknow Publications, 2015)
Topical anesthetics are being widely used in numerous medical and surgical sub-specialties such as anesthesia, ophthalmology, otorhinolaryngology, dentistry, urology, and aesthetic surgery. They cause superficial loss of pain sensation after direct application. Their delivery and effectiveness can be enhanced by using free bases; by increasing the drug concentration, lowering the melting point; by using physical and chemical permeation enhancers and lipid delivery vesicles. Various topical anesthetic agents available for use are eutectic mixture of local anesthetics, ELA-max, lidocaine, epinephrine, tetracaine, bupivanor, 4% tetracaine, benzocaine, proparacaine, Betacaine-LA, topicaine, lidoderm, S-caine patch™ and local anesthetic peel. While using them, careful attention must be paid to their pharmacology, area and duration of application, age and weight of the patients and possible side-effects.